European consensus guidelines on the management of respiratory distress syndrome: 2022 update - ÖZEK, EREN (My University, 2023)
Respiratory distress syndrome (RDS) care pathways evolve slowly as new evidence emerges. We report the sixth version of \"European Guidelines for the Management of RDS \" by a panel of experienced European neonatologists and an expert perinatal obstetrician based on available literature up to end of 2022. Optimising outcome for babies with RDS includes prediction of risk of preterm delivery, appropriate maternal transfer to a perinatal centre, and appropriate and timely use of antenatal steroids. Evidence-based lung-protective management includes initiation of non-invasive respiratory support from birth, judicious use of oxygen, early surfactant administration, caffeine therapy, and avoidance of intubation and mechanical ventilation where possible. Methods of ongoing non-invasive respiratory support have been further refined and may help reduce chronic lung disease. As technology for delivering mechanical ventilation improves, the risk of causing lung injury should decrease, although minimising time spent on mechanical ventilation by targeted use of postnatal corticosteroids remains essential. The general care of infants with RDS is also reviewed, including emphasis on appropriate cardiovascular support and judicious use of antibiotics as being important determinants of best outcome. We would like to dedicate this guideline to the memory of Professor Henry Halliday who died on November 12(,) 2022.These updated guidelines contain evidence from recent Cochrane reviews and medical literature since 2019. Strength of evidence supporting recommendations has been evaluated using the GRADE system. There are changes to some of the previous recommendations as well as some changes to the strength of evidence supporting recommendations that have not changed. This guideline has been endorsed by the European Society for Paediatric Research (ESPR) and the Union of European Neonatal and Perinatal Societies (UENPS).
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; Antenatal corticosteroids; Continuous positive airway pressure; Evidence-based practice; Mechanical ventilation; Non-invasive respiratory support; Nutrition; Oxygen supplementation; Patent ductus arteriosus; Preterm infant; Respiratory distress syndrome; Surfactant therapy; Thermoregulation; EXTREMELY PRETERM INFANTS; PATENT DUCTUS-ARTERIOSUS; POSITIVE AIRWAY PRESSURE; HIGH-FLOW THERAPY; FREQUENCY OSCILLATORY VENTILATION; RANDOMIZED CONTROLLED-TRIAL; BRONCHOPULMONARY DYSPLASIA; ANTENATAL CORTICOSTEROIDS; SUCCESSFUL EXTUBATION; LUNG RECRUITMENT; Antenatal corticosteroids; Continuous positive airway pressure; Evidence-based practice; Mechanical ventilation; Non-invasive respiratory support; Nutrition · Oxygen supplementation; Patent ductus arteriosus; Preterm infant; Respiratory distress syndrome; Surfactant therapy; Thermoregulation